2007
DOI: 10.1177/1532673x07307969
|View full text |Cite
|
Sign up to set email alerts
|

Structuring Gender's Impact

Abstract: The importance of judge gender as a factor in judicial votes continues to attract much scholarly attention. I contribute to the debate on the influence of judge gender by examining the voting behavior of male and female state supreme court justices in three areas of criminal justice. I find that female justices, controlling for institutional, political, and legal constraints, are more likely than are their male counterparts to rule for the criminal defendant and in a broader array of cases than commonly though… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Scholars have examined whether female judges rule differently in subject areas perceived to involve women's issues or areas where women's supposed liberal leanings will make a difference, such as criminal law matters (Songer et al 1994;Jackson 1997;Martin & Pyle 2000). Although the overall picture is unclear (Palmer 2001), the general story appears to be that female judges support the rights of women more strongly than do their male colleagues (Martin & Pyle 2005;McCall & McCall 2007;McCall 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have examined whether female judges rule differently in subject areas perceived to involve women's issues or areas where women's supposed liberal leanings will make a difference, such as criminal law matters (Songer et al 1994;Jackson 1997;Martin & Pyle 2000). Although the overall picture is unclear (Palmer 2001), the general story appears to be that female judges support the rights of women more strongly than do their male colleagues (Martin & Pyle 2005;McCall & McCall 2007;McCall 2008).…”
Section: Introductionmentioning
confidence: 99%
“…1994; Jackson 1997; Martin & Pyle 2000). Although the overall picture is unclear (Palmer 2001), the general story appears to be that female judges support the rights of women more strongly than do their male colleagues (Martin & Pyle 2005; McCall & McCall 2007; McCall 2008).…”
mentioning
confidence: 99%
“…Also, one might expect the effects of gender or race to be more prominent in cases that raise issues related to gender or race. There are studies showing that women judges are more pro-plaintiff in discrimination cases than are men, even controlling for party or ideology (Davis, Haire, and Songer 1993, 132; Songer, Davis, and Haire 1994, 435), and in sexual harassment cases prior to the Clarence Thomas hearings (McCall 2003, 90–93), and there is one study showing that women are more pro-victim (i.e., anti-defendant) in domestic violence cases when the victim is female (McCall 2008, 288). However, gender effects can show up in other types of cases; one study found that women judges on state supreme courts were more likely to vote in a liberal direction than were men in obscenity cases and death penalty cases after taking into account the judge’s political party (Songer and Crews-Meyer 2000).…”
Section: Discussionmentioning
confidence: 99%